sexta-feira, 29 de junho de 2012

Exercício : equação exponencial.

Resolver em $ \Re $ :

$ 4^x\ -\ 3^{x\ -\ \frac{1}{2}}\ =\ 3^{x\ +\ \frac{1}{2}}\ -\ 2^{2x\ -\ 1} $

____________________



Resolução :

$ 2^{2x}\ -\ \frac{3^x}{\sqrt{3}}\ =\ \sqrt{3}\ \cdot\ 3^x\ -\ \frac{2^{2x}}{2} $

$ \frac{2^{2x}\ \cdot\ 3}{2}\ =\ \frac{2^2\ \cdot\ 3^x}{\sqrt{3}} $

$ 2^{2x\ -\ 3}\ =\ 3^{x\ -\ \frac{3}{2}} $

$ 2^{2x\ -\ 3}\ =\ 3^{\frac{2x\ -\ 3}{2}} $

Tomando $ 2x\ -\ 3\ \neq\ 0 \Rightarrow\ x\ \neq\ \frac{3}{2} $ :

$ \sqrt[2x\ -\ 3]{2^{2x\ -\ 3}}\ =\ \sqrt[2x\ -\ 3]{3^\frac{2x\ -\ 3}{2}} $

Temos :

$ 2\ =\ \sqrt{3} $

O que é um absurdo.

Tomando então $ x\ =\ \frac{3}{2} $ :

$ 2^0\ =\ 3^{\frac{0}{2}} $

$ 1\ =\ 1 $

Logo $ S\ =\ \{\frac{3}{2}\} $

Nenhum comentário:

Postar um comentário